FLESHING OUT MEMORY: ROXANE GAY’S HUNGER AS AN EMBODIED NARRATIVE OF SELF- PERCEPTION - Rafseena M.,; Kumar, Ajit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Narratives of selfhood, encompassing diverse experiences, recount the multitude of unaddressed past event/s that have either shaped or ruptured the identity configuration of the subject in irreversible ways. Divided and marginalized based on gender identity and the societal distinction between the sexes, women -signaled as the second sex- have perennially found themselves positioned at the peripheries of socio-cultural representations. The situation exacerbates when addressing the aspects of differential treatment that women undergo due to multiple factors at work. The most prevalent form of modus operandi being that of perpetuating violence on women, women find themselves subjected to subjective and objective violence; the worst being the sexual or physical violence where their body is objectified. Body becomes a site of violence. The present paper titled “Fleshing Out Memory: Roxane Gay’s Hunger as an Embodied Narrative of Self- Perception” delves into the intricate exchange between body and memory as portrayed in Roxane Gay’s memoir Hunger. Challenging the heteronormative expectations, Gay enters into the discourse of recalling, remembering and recording her experiences, where her body becomes a repository of memories - both traumatic and empowering - and how these memories help shape her sense of self. Investigating how the author’s body functions as a vessel for memory, both individual and collective, and how the patriarchal gaze was destructive, this paper tries to locate how the author employs her memoir as a medium to challenge the societal expectations and promote a nuanced understanding of the interconnectedness of body, memory and self-acceptance to build a convenient space of her own in the patriarchal domain.